Fatigue carbohydrate supplementation and skilled tennis performance - Davey, P. R. (2001)
The purpose of this paper is to outline the current research in three main areas: fatigue, carbohydrate supplementation and their influence on skilled tennis performance. Tennis is a typical multiple sprint sport requiring both short-term high intensity activity and general endurance capacity. Players perform a multitude of movements including sprinting, running, jumping, lateral movements, crossover steps and lunges, interspersed with periods of recovery. Tennis, unlike other sports, requires the use of the whole body for stroke production, in contrast to using predominantly the lower body musculature e.g. in distance running. Furthermore, the demands of the tournament schedule also require players to be engaged in matchplay throughout the whole year, with little respite. Such demands make the game both highly physiologically and psychologically demanding and a tough sport to participate in at the `elite` level. Most tennis players and coaches would agree, that in order to be successful in the modern game players need to be able to maintain their skill and fitness over the competitive year, with the ability to perform both accurate and consistent shots. Many factors have been observed by researchers to influence tennis performance and skill such as fatigue, warm up, dehydration, and environment to name but a few. Fatigue is a complex physiological and psychological phenomenon, which is still not fully understood. Research by McCarthy, Williams and Thorpe, (based at Loughborough University) observed players performing a tennis hitting task against a ball machine to volitional fatigue. Skill was measured and consisted of consistency, accuracy and error (balls hit out). The research findings revealed that players` accuracy diminished by approximately 70% from the start of the test to the point of volitional fatigue. In a further study a similar decline in skill was observed when a flavoured water placebo was consumed throughout simulated matchplay followed by a hitting test to exhaustion. However when players ingested a carbohydrate-electrolyte beverage (CHO-E) (6.9% solution) throughout simulated matchplay, players were able to sustain their skilled performance with no decrement in skill whatsoever. Blood glucose concentration was maintained (Euglycaemia) throughout the CHO-E trial. Thus the ingestion of a CHO-E beverage provided the players with a metabolic advantage, supplying sufficient energy for the production of strokes in a simulated match and hitting performance test. When a CHO-E beverage was not supplemented, not only did players` blood glucose concentration exhibit (in some cases) a hypoglycaemic response, but skill was also negatively affected. Muscle glycogen sparing may have been an important mechanism in the sustenance of skill in this study, especially in the later stages of the CHO-E trial. Also of interest was a decline in grip strength over the duration of the test. This decline was observed in both the hitting and non-hitting hands and suggested a neural / central component to the fatigue model. Although not significant, a trend for a smaller decline in grip strength was observed in both hands in the CHO-E trial. Tennis players, at the elite level are constantly striving to improve their performance and gain an advantage over their opponents. Players will not however be able to achieve such an aim, nor perform optimal training, if attention is not given to nutritional support. It is essential that fatigue in tennis players be kept to a minimum, in order to optimise their talent and prevent a decrement in their skill.